Opening up learning conversations: Including patients. Issue 10 (17th July 2022) - Sehlbach, Carolin; Rowland, Paula
Abstract : Sehlbach and Rowland describe the credibility of patient feedback along with its benefits for patients and learners while shedding light on vulnerability and risks that need to be contemplated.